2019
DOI: 10.1177/1043986219832132
|View full text |Cite
|
Sign up to set email alerts
|

Hot Spots of Crime Are Not Just Hot Spots of Crime: Examining Health Outcomes at Street Segments

Abstract: In this paper we seek to identify whether the relationship between health disparities and crime occurs at a micro geographic level. Do hot spot streets evidence much higher levels of mental and physical illness than streets with little crime? Are residents of crime hot spots more likely to have health problems that interfere with their normal daily activities? To answer these questions, we draw upon a large National Institutes of Health study of a sample of hot spots and non-hot spots in Baltimore, Maryland. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 75 publications
1
21
0
Order By: Relevance
“…Recently, Weisburd et al () examined mental health at a microgeographic level using residential surveys collected on 449 street segments in Baltimore. They found that residents of violent crime hot spots had an increased likelihood of depression and posttraumatic stress disorder (PTSD) symptoms compared to residents living on nonhot spot streets (see also Weisburd and White, ). Additionally, Vaughan et al () examined why calls involving an emotionally disturbed person (EDP) might cluster in places different from that of crime generally.…”
Section: Mental Healthmentioning
confidence: 99%
“…Recently, Weisburd et al () examined mental health at a microgeographic level using residential surveys collected on 449 street segments in Baltimore. They found that residents of violent crime hot spots had an increased likelihood of depression and posttraumatic stress disorder (PTSD) symptoms compared to residents living on nonhot spot streets (see also Weisburd and White, ). Additionally, Vaughan et al () examined why calls involving an emotionally disturbed person (EDP) might cluster in places different from that of crime generally.…”
Section: Mental Healthmentioning
confidence: 99%
“…This paucity of research is unfortunate, since people with mental health problems may not only perceive crime, safety, and the police differently (cf. Newman, ; Yanos, Felton, Tsemberis, & Frye, ), but they are also more likely to live in, and be affected adversely by, the particular environments where these issues are more prevalent (Latkin & Curry, ; Ross, ; Weisburd et al, ; Weisburd & White, ).…”
Section: Introductionmentioning
confidence: 99%
“…see Weisburd, ; Weisburd, Hinkle, Famega, & Ready, ) and also with specific types of crime such as drug markets (Weisburd & Green, ; Weisburd & Mazerolle, ), juvenile crime (Weisburd, Morris, & Groff, ), gun violence (Braga, Papachristos, & Hureau, ), and mental health related calls (White & Goldberg, ). Furthermore, a recent study found that individuals who live in violent crime hot spots are more likely to have depression and/or PTSD (Weisburd et al, ; see also Weisburd & White, ). Because residents who live in crime hot spots are more likely to have mental health problems and come into contact with the police, it is important to examine their perceptions specifically.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The city is significantly known for high crime rate which ranks higher than the national average. A series of news reports and few crime studies ( [23], [24]) depict the surge of violent crimes since 2011, in particular of homicides. The lowest homicide toll of 196 was recorded in the year 2011, and since then there has been a steady upward trend.…”
Section: Baltimore Crime Datamentioning
confidence: 99%